Exploring the structural, optical, dielectric and magnetic properties of rare earth samarium doped Ca-Mg based Ca0.5Mg0.5Fe12−xSmxO19 ferrite nanoparticles - Alshammari, Basmah H.; Alanazi, Kaseb D.; Asif, Sana Ullah; Nawaz, Usman (Inorganic chemistry communications, 2024)
Exploring the structural, optical, dielectric and magnetic properties of rare earth samarium doped Ca-Mg based Ca0.5Mg0.5Fe12−xSmxO19 ferrite nanoparticles. [Display omitted] •A series of Samarium (Sm) doped Ca/Mg hexaferrite samples were gabricated.•Structure reveals a consistent magnetoplumbite phase across all samples.•The higher concentrations of samarium resulted in reductions of dielectric loss (ε″) and dielectric constant (ε′).•The material possesses promising magnetic parameters falling within the ranges of 31.52–37.77 emu·g−1 for Ms, 18.16–21.53 emu·g−1 for Mr, and 2.088–2.243 kOe for Hc. The emergence of M-type hexaferrite presents an encouraging alternative to rare earth magnets, due to its economic feasibility and outstanding magnetic properties. This makes it a viable option for applications in the electric automotive and magnetic industry applications. In this study, we utilized a sol–gel auto-combustion technique to synthesize a series of samarium (Sm) doped calcium-magnesium (Ca-Mg) hexaferrite samples having chemical formula Ca0.5Mg0.5Fe12−xSmxO19 (x = 0.00, 0.05, 0.10, 0.15, and 0.20). The XRD analysis confirmed the crystal structure of the synthesized materials, revealing a consistent magneto-plumbite phase across all samples. Scanning electron microscopy (SEM) investigations further confirmed the homogeneous distribution and agglomeration of nanostructures. FTIR analysis identified the presence of two primary absorption bands in Ca-Mg hexaferrites with both bands exhibiting a shift towards lower frequency ranges with increasing doping levels. The dielectric loss (ε″) and dielectric constant (ε′) were higher at lower frequencies but decreased as the frequency increased. Additionally, higher concentrations of samarium resulted in further reductions in both dielectric loss (ε″) and dielectric constant (ε′). Notably, saturation magnetization (Ms) and remanence (Mr) values demonstrated an increasing trend with higher degrees of Sm+3 substitution, while coercivity (Hc) values exhibited relative stability. Our findings indicate that these materials possess promising magnetic parameters falling within the ranges of 31.52–37.77 emu·g−1 for Ms, 18.16–21.53 emu·g−1 for Mr, and 2.088–2.243 kOe for Hc, suggesting their potential utility across diverse applications including permanent magnets used in electric vehicle motors, storage devices, microwave components, and electromagnetic radiation absorbers.